1983
DOI: 10.1042/cs0640383
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Insulin on the Rise in Blood Pressure and Plasma Aldosterone after Angiotensin II in Normal Man

Abstract: 1. The effect of an intravenous infusion of insulin [2.5 units h-1 (m2 of body surface area)-1] on the rise in blood pressure and plasma aldosterone after intravenous angiotensin II (5, 10, and 20 ng min-1 kg-1) was investigated in six healthy, sodium-loaded men. 2. Serum insulin reached 96.8 +/- 18.1 mu-units/ml (control: 7.0 +/- 1.5 mu-units/ml) and serum potassium fell from 4.2 +/- 0.2 mmol/l to 3.6 +/- 0.2 mmol/l (P less than 0.005). 3. Hyperinsulinaemia increased (P less than 0.05) the secretion of aldost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
1
1

Year Published

1984
1984
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 0 publications
0
20
1
1
Order By: Relevance
“…39 In contrast, and once again showing important differences between fructose-or sucrose-fed models, in obese fatfed dogs aldosterone is progressively increased in parallel with sodium accumulation. 8 To explain this inadequate increase, it has been argued that insulin enhances angiotensin-stimulated aldosterone secretion 41 ; however, it is unclear why in the fructose-or sucrose-fed models, which are comparably hyperinsulinemic, aldosterone is not similarly increased.…”
Section: Fructose-feeding and Hypertension Mechanismsmentioning
confidence: 99%
“…39 In contrast, and once again showing important differences between fructose-or sucrose-fed models, in obese fatfed dogs aldosterone is progressively increased in parallel with sodium accumulation. 8 To explain this inadequate increase, it has been argued that insulin enhances angiotensin-stimulated aldosterone secretion 41 ; however, it is unclear why in the fructose-or sucrose-fed models, which are comparably hyperinsulinemic, aldosterone is not similarly increased.…”
Section: Fructose-feeding and Hypertension Mechanismsmentioning
confidence: 99%
“…In humans, results regarding the effects of insulin on cardiovascular reactivity are also conflicting. Vierhapper et al 14 reported that intravenous insulin with the euglycemic clamp method did not alter blood pressure responses to Ang II in normal humans. Yamamoto et al 13 reported that intravenous insulin attenuated blood pressure responses to phenylephrine and Ang II in diabetic men without neuropathy.…”
Section: Effect Of Insulin On Vascular Reactivity To Pressor Agentsmentioning
confidence: 99%
“…Most of these studies demonstrated that insulin decreased or did not alter vascular reactivity to vasoconstricting stimuli. 13 ' 14 However, Gans et al 15 recently reported that intravenous insulin augmented blood pressure responses to norepinephrine but not to Ang II. Thus, reported results are conflicting.…”
mentioning
confidence: 99%
“…However, there are limited data on the microvascular effects of insulin in man. Euglycaemic hyperinsulinaemia in healthy subjects has been reported to augment cardiovascular reactivity to noradrenaline [19], while no effect was demonstrated with angiotensin II [19,20]. Moreover, acute increases in plasma insulin within the physiological range have shown conflicting responses in forearm vasodilation [21,22], but with no increase in blood pressure despite increased sympathetic neural outflow [21] and a marked increase in forearm noradrenaline release [22].…”
mentioning
confidence: 99%